Heterologous Expression Of Xylanase Gene From Klebsiella Pneumoniae In E. Coli Bl21 (De3) For Potential Use In Green Technology - Mohd Hasnain, Hussain; Suhaila, Bt Zainol; Chong, Nikson Fatt Ming; Awang Ahmad Sallehin, Awang Husaini (UNIVERSITI MALAYSIA SARAWAK (UNIMAS), 2013)
A xylanolytic bacterium was isolated from sago plantation humus. Isolation and characterization of xylanase DNA sequence showed a total length of 642 bp. The full length xylanase gene was cloned in pSTAG vector and expressed in E. coli BL21 (DE3). In silico characterization determines the recombinant xylanase has a molecular weight of 23.9 kDa. The activity of crude recombinant xylanase was 2.015 U/mL, which was higher than the crude native xylanase activity that was only 0.642 U/mL at maximum. Staining of the birchwood xylan agar plate with Congo red showed a clearing zone around E. coli BL21 (DE3) that has positive recombinant xylanase even without the addition of IPTG, implying leaky expression had occurred. Further analysis showed the existence of two forms of the xylanase. These xylanases were enzymes with the size of 25kDa that accumulates in the cell, and the other as a 20kDa mature extracellular xylanase.